Migration, Displacement, and Higher Education Now What? - Murray, Brittany; Brill-Carlat, Matthew; Höhn, Maria (Political Pedagogies, 2023)
This open access book is a nuanced introduction to Forced Migration Studies and a toolkit for faculty and undergraduate students, with a special emphasis on community-engaged learning. Experts from the social sciences, humanities, arts, and experimental sciences offer interdisciplinary perspectives to translate critical analysis into concrete action. The collection highlights activists, artists, and educators who have initiated projects in cooperation with and for the benefit of populations affected by migration and displacement. Together, these contributions powerfully articulate the relevance of the liberal arts and social sciences in preparing students to meet increasingly interconnected global challenges such as forced migration, climate change, and Covid-19.